Oral administration of Sargassum polycystum extracts stimulates immune response and increases survival against Aeromonas hydrophila infection in Oncorhynchus mykiss - Sönmez, Adem Yavuz; Bi̇len, Soner; Taştan, Yiğit; Serag, Karen Joy B.; Toring, Concepcion C.; Romero, Jumelita B.; Kenanoğlu, Osman Nezih; Terzi, Ertugrul (Elsevier BV, 2021)
This study investigated the immunomodulatory effects of Sargassum polycystum extract administration in rainbow trout (Oncorhynchus mykiss). S. polycystum methanolic extract was administered orally using feeding needles to individual rainbow trout at the dose of 0 (control), 1 (S1), 3 (S3) and 5 (S5) mg/100 μl/per fish twice a day for 7 days. On 1st, 5th, 3rd and 7th day, blood and tissues were collected from the fish and changes in humoral immune responses and immune-related gene expressions were determined. The result of oxidative radical production showed no difference during early stage of the experiment and was lately decreased (P < 0.05). Lysozyme activity increased on 3rd and 7th day of the study in S5 fish group and on 5th day in S3 group compared to control (P < 0.05). Myeloperoxidase activity had an increased level on the 1st and 3rd day in S1, S5 and S5 fish groups, respectively. IL-1β gene was significantly up-regulated in kidney and intestine in all experimental groups (except on the 1st day, in the intestine of S5 fish group) compared to control (P < 0.05). IL-8 gene expression was elevated on 1st and 3rd day in kidney of all experimental fish groups. IL-6 transcript enhanced in a dose-dependent manner on 3rd and 7th day. IL-10 and IL-12 genes were also up-regulated. Survival in all treated fish groups challenged with Aeromonas hydrophila was significantly increased compared to that of control. The highest survival rate was recorded in S5 fish group (83.65%) followed by S3 fish group (82.62%). Our results suggest that S. polycystum aqueous methanolic extract is an effective immunostimulant and provide protection against A. hydrophila infection in rainbow trout at a dose of 3-10 mg/20 g body weight/day.
Keywords: Sargassum; Administration, Oral; Complex Mixtures; Aeromonas hydrophila; Fish Diseases; Adjuvants, Immunologic; Oncorhynchus mykiss; Animals; Cytokines; Muramidase; Gram-Negative Bacterial Infections; Peroxidase; 3. Good health